The Dynamics of Asy-syuro Mosque’s Role in Cipari Village in 1912-2015 as Social Studies Learnings Source - Fauziah, Nurul (International Journal Pedagogy of Social Studies, 2019)
This study was conducted since there is a problem of limited social studies learning source for junior high school or SMP. Mostly, teachers only provide textbooks or other learning material, but do not use environment as the source of social studies learning. Thus, learning source which uses environment is highly needed, such as role Dynamics of Asy-syuro Mosque in 1912-2015, which aims to increase students’ enthusiasm in learning social studies in class and to make students understand the lesson more easily because they can see it directly. In this research, the case study method was used because the researcher carefully observed the role of Asy-syuro Mosque in the Pre Independence (1912-1945) and the Post-Independence (1949-2015) periods. Data collection technique of this study was through Literature study, Observation, interview, and documentation study. The subjects of this study are the family of the mosque’s founder, Asy-syuro Mosque management, Cipari village’s elders, social studies teachers, and students of MTs Ponpes Cipari. Based on the research, it is found that Asy-syuro Mosque had a quite significant role change in seven aspects (Ritual, Social, Economy, Education, Da’wah, Politics, and Health). The role of Asy-Syuro Mosque in politics in 1912, 1945 and 1949 has values and meanings of great fighting, togetherness, cooperation, and nationalism soul. This case is included into learning source "Message" component. Meanwhile, Asy-Syuro Mosque's role in other aspects, has piety, responsibility, concern, honesty, values and as the application of Social Interaction and Social Motives Economic Action materials. These are included into learning source "Environment" type. Asy-Syuro Mosque is a kind of "Learning Resources by Utilization" which uses environment or surroundings and is relevant to social studies learning material.